EFFECTIVENESS OF THE TEAM GAMES TOURNAMENT LEARNING MODEL ASSISTED BY QUIZWHIZZER ON LEARNING OUTCOMES AND JOYFUL LEARNING OF PANCASILA EDUCATION STUDENTS OF ELEMENTARY SCHOOL - Pujiana, Sintiya; Aeni, Kurotul (STKIP Citra Bakti, 2026)
This study aims to analyze the differences in joyful learning and students’ learning outcomes between those taught using the Teams Games Tournament (TGT) model integrated with Quizwhizzer and those taught using conventional methods, as well as to examine the effectiveness of the model on joyful learning and learning outcomes in Pancasila Education. This study employed a quasi-experimental design with a nonequivalent control group design involving 37 fifth-grade students at SDN Wonosari 03, Semarang City, divided into an experimental class and a control class. Data were collected through interviews, a joyful learning questionnaire, and a learning outcomes test. The questionnaire consisted of 20 valid and reliable Likert-scale items (Cronbach’s Alpha = 0.731), while the test consisted of 20 valid and reliable multiple-choice items (Cronbach’s Alpha = 0.770). The results revealed a significant difference in joyful learning between the experimental and control classes based on the independent samples t-test (Sig. (2-tailed) = 0.000 < 0.05). The N-Gain score for joyful learning in the experimental class was 0.71 (high category), compared to 0.19 (low category) in the control class. For learning outcomes, the experimental class obtained an N-Gain of 0.58 (moderate category), while the control class obtained 0.29 (low category). These findings indicate that improvements in both joyful learning and learning outcomes were higher in the experimental class than in the control class. It can be concluded that the TGT model integrated with Quizwhizzer has a positive effect on improving students’ joyful learning and learning outcomes compared to conventional instruction.